Using video in teacher education - Brophy, Jere E. (Amsterdam ; London : JAI, 2003)
This book features contribution from people who have developed and used video in teacher education. The focus is on video as opposed to other technology (e-mail, etc.) and its use in teacher education. The video can be stored on videotapes, CD-Rom, DVD, or computer drives, and it can be used in either preservice or inservice teacher education/professional development programs. Contributors explain the nature of the video they use in their teacher education programs or courses and talk about how they use it, focusing in particular on principles for: making the videos (decisions about how and what to capture on video, the degree to which the teaching should be scripted, whether it should be shown uninterrupted or segmented and edited, and so on), and principles for using the video in the teacher education program (why and how it is used at what points in the program, how viewings are structured and scaffolded by the teacher educator, and so on).
New perspectives on the role of video in teacher education / Miriam Gamoran Sherin -- Quality visions and focused imagination / Traci Bliss and Anne Reynolds -- Using video to create a vision for powerful discussion teaching in secondary social studies / Diana E. Hess -- Designing and developing a video-case based interactive program for English language arts teacher preparation / Liz Campbell Stephens -- Videocases in elementary science teacher preparation / Sandra K. Abell and Katherine S. Cennamo -- For the enrichment of practical knowledge: food practice and useful theory for future primary teachers / Wil Oonk, Fred Goffree and Nico Verloop -- Designing a virtual K-2 classroom literacy tour: learning together as teachers explore "best practice" / Cheryl L. Rosaen, Christine Degnan, Teresa VanStratt and Kathryn Zietlow -- Linking on-line video and curriculum to leverage community knowledge / Barry J. Fishman -- Designing for teacher learning: video-based curriculum design / Deidre M. Le Fevre -- Using video as an object of inquiry for mathematics teaching and learning / Nanette Seago -- Discussion / Jere Brophy.
Includes bibliographical references.
Description based on print version record.
Keywords: Teachers -- Training of; Video tapes in education; Teacher training; Educational equipment & technology, computer-aided learning; Education -- Teaching Methods & Materials -- General